Divergent rhodium-catalyzed electrochemical vinylic C–H annulation of acrylamides with alkynes - Yi-Kang Xing (Nature Portfolio, 2021)
α-Pyridones and α-pyrones are ubiquitous structural motifs found in natural products and components of biologically active small molecules. Here, the authors report an oxidant-free Rh-catalyzed electrochemical divergent vinylic C–H annulation of acrylamides with alkynes to α-pyridones and cyclic imidates.